MACROECONOMIC ENVIRONMENT OF UKRAINE AND DYNAMICS OF ITS DEVELOPMENT IN THE CURRENT REALITIES - Alina Herasymenko (Izdevnieciba "Baltija Publishing", 2023)
The purpose of the article is to analyse the key macroeconomic factors that determine the general state and dynamics of the macroeconomic environment of Ukraine in modern realities. The methodological basis of the study is the generalisation of the results of applied research in the field of economics, scientific works, statistical data, which highlight some aspects of the development of the modern Ukrainian economy. Results. The modern conditions in which the Ukrainian economy is forced to operate against the backdrop of military escalation have a corresponding impact on the state and dynamics of its macroeconomic environment, and thus on the level of economic activity of all business entities. The article analyses the peculiarities of the development of the macroeconomic environment of Ukraine in the period before the full-scale military invasion and in the first year of the war. The study analyses such structuring macroeconomic factors of the macroeconomic environment of Ukraine as the availability and accessibility of natural resources, the sectoral composition of the national economy, the state and development of the markets for goods and services, the state and development of the financial market, and analyses the main indicators of economic development. Practical implications. The practical results can be used as a basis for further research: on ways to improve the macroeconomic environment of Ukraine; on financial support for the recovery of the national economy and, accordingly, improvement of the dynamics of the macroeconomic environment of Ukraine; on the prospects for transformation of certain macroeconomic factors of the macroeconomic environment: in particular, in the electricity market by introducing renewable energy technologies; in the markets for goods and services by introducing the principles of the "green" economy in industrial production; in the sectoral composition of the national economy by increasing the role of technology and innovation in economic activity, etc. Value/originality. The results of the study provide a deeper understanding of the role and importance of the dynamics of the country's macroeconomic environment in the economic activity of business entities, as well as an assessment of the economic consequences of the war on the state of Ukraine's macroeconomic environment.